Biological Phosphorus Recovery: Review of Current Progress and Future Needs: Yang et al. (1st December 2017) - Yang, Yu; Shi, Xu; Ballent, Wendy; Mayer, Brooke K.
ABSTRACT: : This review summarizes the main species of polyphosphate accumulating organisms (PAOs) and algae, illustrates their pathways and key enzymes, discusses biological phosphorous (P) recovery from dilute waters, and identifies research avenues to encourage adoption and implementation. Phylogenic analysis indicates that the Proteobacteria phylum plays an important role in enhanced biological phosphorus removal (EBPR). The use of meta‐transcriptome analysis and single cell‐based techniques to help overcome the challenges associated with non‐PAO competition was discussed. For algae capable of luxury phosphorus uptake, fundamental research is needed to illustrate the phosphorus regulation process and key proteins involved. Emerging technologies and processes have great potential to further advance phosphorus recovery, including combined PAO/algae reactors, bioelectrochemical systems, and biosorption by phosphorus binding proteins. As the paradigm shifts toward holistic resource recovery, research is needed to explore P+ recovery with other resources (e.g., metals from sludge), using a combination of biological and chemical approaches.